Noises yet to know- Post ironical consequences of rortian metaphorizing - Lavagnino, Nicolás Alejo (2012)
In 1913 Ezra Pound wrote a beautiful and brief poem entitled “In a Station of the Metro”. Those brief and epigrammatic lines, almost in the form of a haiku, went: “The apparition of these faces in the crowd / petals on a wet, black bough”. I will take this poem as an excuse to discuss the role of metaphor in a given space of linguistic practices. In particular, I am interested in following the relations established by Richard Rorty between metaphor and irony, in the context of the characterization of his version of pragmatism. Those relations should be of use to enlighten aspects of the fourteen words that conforms Pound’s small worldview and, at the same time, show some of the slides in meaning that must take place for the Rortian metaphorical-ironical compound to be of service to the general vision of the verbal practice in which such compound is inserted. Those slides, at the same time, will allow me to show some tensions regarding the Davidsonian approach to metaphor, to which Rorty is expressly affiliated, and will lead me towards a strictly tropological interpretation of the Rortian experiment. In that interpretation, two things will stand out. On the one hand, that Rorty’s pragmatism has plenty to offer to tropology as a study of ordinary linguistic practices but, on the other hand, that tropology in the sense of a study of the interrelations between tropes can help overcome some of the limitations which, I assert, surround and threaten the Rortian interpretation of metaphor.